Metabolic effects of Bauhinia forficata leaves infusion in Drosophila melanogaster fed with high sucrose diet (Research, Society and Development, 2020)
Increased dietary carbohydrate consumption can cause several biochemical imbalances. Bauhinia forficata (BF), known in folk medicine as “cow paw”, is widely used because of its antihyperglycemic action. The aim of this study was to evaluate the metabolic effects of BF leaves infusion in D. melanogaster fed with a high sucrose diet. For this, different sucrose concentrations were added to the standard culture medium and the BF tea was administered through filter paper. Weight variation was determined by comparing the weight of the flies at different sucrose concentrations with the control flies. After three days of treatment, flies were euthanized for biochemical analysis. Results showed that female flies fed 40% sucrose and male flies fed 30% showed significantly higher glucose levels compared to the same concentration group treated with BF tea. Triglyceride levels were significantly increased in females treated with 30% sucrose as compared to control. There was no significant increase in female weight as sucrose concentration increased. Superoxide dismutase activity was higher in females, although not significant. BF tea had no significant effects on insect body weight. In conclusion, the data suggest that a high carbohydrate diet may alter triglyceride and glucose levels in D. melanogaster and that BF tea may be helpful in lowering glucose.